Design a Web Platform to manage environmental monitoring information to be used in multicriteria evaluations of Green Infrastructures. (May 2019) - Gallo, R; Ristorto, G; Bojeri, A; Zorzi, N; Rinaldi, M F; Sauli, G; Mazzetto, F
Abstract: The aim of the WEQUAL project "WEb service centre for QUALity multidimensional design and tele-operated monitoring of Green Infrastructures") is the development of a system able to support a quick environmental monitoring of watercourses where new hydraulic structures are intended to be built, encouraging the identification of design solutions supporting the diffusion of Green Infrastructures (GI). The WEQUAL's idea is to organize a service centre where users (designer, technician, researcher) can access the service through a personal account and carry out an assessment of alternative GI projects. Through some automatic procedures, accessible via a suitable web platform, a set of algorithms may be applied to process raw data collected by an UAV (Unmanned Aircraft Vehicle) equipped with a 3D Lidar, multispectral camera and RGB camera, for the purpose of calculating the WEQUI Index. The WEQUI index is used to assesses the eco-morphological status of the monitored watercourse, taking advantage from data related to NDVI index, Digital Terrain Model (DTM), Digital Surface Model (DSM) and a 3D point cloud classification. The computed value of the WEQUI index may be used to assess the eco-morphological quality at ex-ante and ex-post river stabilization or protection intervention. The platform will provide a shared environment integrating indices calculations and environmental-parameters assessment for multidimensional evaluations.